The Childfree Phenomenon in Some Influencers - Siti Zulaikha (ARRUS Journal of Social Sciences and Humanities, 2023)
Decision to not have a child cause negative stigma social. The perspective of married couple that decide to not have child called childfree. Not having children is not a kind of new concept; many married couple in developed countries already make this choice. The married couple have a role from decision to not have child in their family life. It is because related to their reproduction things. Islam already discuss about rights of husband and wife to have a child. The author interested to conduct the research to study phenomenon about not to have children from the woman reproduction perspective rights in Islam from this phenomenon. Method used in this research was the library research with Juridical Normative approach. Data collection technique included documentation and the analysis used content analysis method. Decision to not have a child need to have deep consideration. One of the implementations of rights reproduction, especially rights to refuse pregnancy is a choice to not have a child. In order to implement this right, a household must adopt an idea about relationship between husband and wife. Decision to not have a child need to be discussed between husband and wife. Both of them, most important the woman, must be honest ​​about the reason they do not want to have child. So as not to harm either party, the reason must be accompanied with convincing basic justification.